Intrinsic glue and Wilson lines within dressed quarks - Costa, Caroline S. R. [UNESP]; Freese, Adam; Cloët, Ian C.; El-Bennich, Bruno; Krein, Gastão [UNESP]; Tandy, Peter C. (American Physical Society (APS), 2021)
We construct a quark target model (QTM) to incorporate intrinsic glue into effective low-energy models of QCD, which often contain only quark degrees of freedom. This method guarantees the gauge invariance of observables order by order in the strong coupling. The quark and gluon PDFs for the dressed quarks are obtained in the QTM at leading order. We demonstrate gauge invariance of the results by comparing both covariant and light cone gauges, with the former including an explicit Wilson line contribution. A key finding is that in covariant gauges the Wilson line can carry a significant amount of the light cone momentum. With coupling strength and dressed quark mass , we find quark and gluon momentum fractions of and , where the Wilson line contribution to the quark momentum fraction is . We use the on-shell renormalization scheme and find that at one loop this Wilson line contribution does not depend on the covariant gauge but does vanish in light cone gauge as expected. This result demonstrates that it is crucial to account for Wilson line contributions when calculating quantum correlation functions in covariant gauges. We also consider the impact of a gluon mass using the gauge invariant formalism proposed by Cornwall, and combine these QTM results with two quark-level models to obtain quark and gluon PDFs for the pion.